Evolution of weedy giant ragweed (Ambrosia trifida): Multiple origins and gene expression variability facilitates weediness. Issue 12 (8th December 2022) - Li, Bo; Gschwend, Andrea R.; Hovick, Stephen M.; Gutek, Amanda; McHale, Leah; Harrison, S. Kent; Regnier, Emilie E.
Abstract: Agricultural weeds may originate from wild populations, but the origination patterns and genetics underlying this transition remain largely unknown. Analysis of weedy‐wild paired populations from independent locations may provide evidence to identify key genetic variation contributing to this adaptive shift. We performed genetic variation and expression analyses on transcriptome data from 67 giant ragweed samples collected from different locations in Ohio, Iowa, and Minnesota and found geographically separated weedy populations likely originated independently from their adjacent wild populations, but subsequent spreading of weedy populations also occurred locally. By using eight closely related weedy‐wild paired populations, we identified thousands of unique transcripts in weedy populations that reflect shared or specific functions corresponding, respectively, to both convergently evolved and population‐specific weediness processes. In addition, differential expression of specific groups of genes was detected between weedy and wild giant ragweed populations using gene expression diversity and gene co‐expression network analyses. Our study suggests an integrated route of weedy giant ragweed origination, consisting of independent origination combined with the subsequent spreading of certain weedy populations, and provides several lines of evidence to support the hypothesis that gene expression variability plays a key role in the evolution of weedy species. Abstract : We investigated the population genetic structure and expression patterns of giant ragweed plants sourced from crop and noncrop habitats across the Eastern Corn Belt of the USA, where this native species appears to have undergone one or more evolutionary transitions to succeed in crop fields as a major agricultural weed. The results of our study suggest an integrated route of weedy giant ragweed origination, consisting of independent origination combined with the subsequent spreading of certain weedy populations, and provide several lines of evidence to support the hypothesis that gene expression variability plays a key role in the evolution of weedy species.